Glad2Glow Purchase Intent: TikTok Marketing through Customer Brand Engagement and Brand Image - Marbakh, Nisha; Rahmiati, Rahmiati (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The rapid development of social media has significantly transformed its role, evolving from a mere communication and entertainment tool to a powerful platform for business, particularly in marketing, enabling businesses to reach a broad consumer base. This study investigates the influence of TikTok's social media marketing on consumer purchase intention, mediated by consumer brand engagement and brand image, focusing on the Glad2Glow skincare brand. The research employs a quantitative approach, utilizing a questionnaire distributed to 385 TikTok users familiar with Glad2Glow. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that TikTok's social media marketing positively and significantly impacts consumer purchase intention, with consumer brand engagement and brand image acting as significant mediators in this relationship.